To the General Assembly : Gentlemen, As I am not influenced by party zeal, nor guided by personal interest, I should have viewed your actions with contempt or indifference . - Farmer, (and once a grand juror) of Orange County ([publisher not identified], 1772)
Renewing charges of dishonesty as levelled against New York Assemblyman John De Noyelles in a paper entitled "To the public," signed "Brutus" and dated Jan. 28, 1772 (Evans 12336), and denouncing the General Assembly's inquiry into the matter in its Votes and proceedings, Jan. 7-Mar. 24, 1772 (Evans 12484)